A Joint DFT and Experimental Study of an Imidazolidinone Additive in Lithium-Ion Cells. Issue 15 (11th November 2019) - Gauthier, Roby; Hall, David S.; Taskovic, T.; Dahn, J. R.
Abstract : Electrolyte additives are a practical route to improving the lifetime and performance of lithium-ion cells. It is not well understood what makes a good additive; thus, the discovery of new additives poses a significant challenge. Computational methods have the potential to streamline the search for new additives, but it is important to compare predicted additive behavior with experimentally measured results. A new electrolyte additive, 1, 3-dimethyl-2-imidazolidinone (DMI), has been evaluated in LiNi1-x-y Mnx Coy O2 (NMC)/graphite pouch cells as a single additive and with the co-additive vinylene carbonate (VC). This work compares the density functional theory (DFT)-predicted behavior of DMI with experimental results, including differential capacity analysis (dQ/dV), electrochemical impedance spectroscopy (EIS), high-temperature storage, gas chromatography-mass spectrometry (GC-MS) and long-term cycling tests. The DFT-calculated reduction potential of DMI is −0.63 V vs Li/Li +, consistent with the experimental observation that it reduces at a lower potential than ethylene carbonate (EC), ∼0.80 V vs Li/Li + . Although DMI turns out not to be a competitively useful additive, the good match between many aspects of the experimental results and theoretical predictions is a good indication that it is possible to understand aspects of the behavior of additives. This can guide future researchers.